Facile synthesis of Sm2S3 diffused nanoflakes and their pseudocapactive behavior. Issue 4 (May 2015) - Kumbhar, V.S.; Lokhande, A.C.; Gaikwad, N.S.; Lokhande, C.D.
Abstract: The Sm2 S3 thin films with diffused nanoflakes morphology are prepared by an environment-friendly facile chemical synthesis method and used in electrochemical supercapacitors. The structural, elemental and surface morphological characterization are carried out using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FESEM) and wettability techniques. The FESEM images show tree root like distribution of flakes with average flake width of about 80 nm. The film surface is lyophilic with propylene carbonate contact angle of 21°. The supercapacitive measurements are carried out through cyclic voltammetry, galvanostatic charge-discharge and electrochemical impedance spectroscopy (EIS) techniques. The Sm2 S3 film electrode exhibited a highest specific capacitance ( C s ) of 213 Fg −1 at 5 mVs −1 scan rate in LiClO4 -propylene carbonate electrolyte. Asymmetric nature of charge–discharge curves confirmed pseudocapacitive behavior of electrode with energy and power densities of 39.39 Whkg −1 and 4.33 kWkg −1, respectively. An equivalent series resistance of 0.44 Ωcm −2 indicated negligible ohmic losses in charge storage. An electrochemical stability of 81.47% is retained after 1000 cycles indicating that Sm2 S3 is a promising candidate for supercapacitor application.